THE PROBLEM OF THE CATEGORY OF TENSE IN MODERN ENGLISH - Abdurashidova, Zebiniso; Xoldorova, Hilola (Educational Research in Universal Sciences, 2023)
This article provides information on Shakespeare’s morphology. His poems are morphologically analyzed and sources related to poetry are presented. Grammatical problems are studied.In addition, in this article Shakespeare’s works are analyzed.